2010
DOI: 10.1177/1403494809364561
|View full text |Cite
|
Sign up to set email alerts
|

Locality differences of sickness absence in the context of health and social conditions of the inhabitants

Abstract: Area-specific practice, or habitus, as an independent determinant of sickness absence is discussed and an explicitly sociological context is recommended for debates about ''best sickness absence practices'' and corresponding intervention measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Future research should include more diverse industries, along with specific assessments of job classifications in order to determine the degree to which occupational activities or cultural factors influence both weight change and absenteeism. For example, research in Finland recently indicated that substantial variation exists in the underlying local rates of workplace absenteeism, and such regional-sociological proclivities can be used to inform more targeted worksite health interventions [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Future research should include more diverse industries, along with specific assessments of job classifications in order to determine the degree to which occupational activities or cultural factors influence both weight change and absenteeism. For example, research in Finland recently indicated that substantial variation exists in the underlying local rates of workplace absenteeism, and such regional-sociological proclivities can be used to inform more targeted worksite health interventions [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Sickness absence is not likely to be strongly associated with features of the working conditions or the work community. The psychosocial environment outside work may also have effects on sickness absence [14]: for example, sickness absence seems to depend on a person's close community [30], as well on the local community in which an individual lives [31]. …”
Section: Discussionmentioning
confidence: 99%
“…However, some later studies adjust for occupation (Mastekaasa 2005;Nordström et al 2016) or distinct aspects of the work environment (Bryngelson et al 2011;Hensing and Alexanderson 2004;Jonsson et al 2013). Indeed, occupation is a potent factor for worker health encompassing both occupational and socioeconomic conditions playing a crucial role for differences in sick leave (Lidwall et al 2018;Mastekaasa 2005;Virtanen et al 2010). As employers have a key role in addressing preventive work environment measures, branches are also crucial for the identification of where to intervene (Berglund et al 2019;Gaspar et al 2018;Irastorza et al 2016;Kristman et al 2016;Marshall et al 1997).…”
Section: Occupational Working Conditions and The Contextual Factor Ofmentioning
confidence: 99%
“…As employers have a key role in addressing preventive work environment measures, branches are also crucial for the identification of where to intervene (Berglund et al 2019;Gaspar et al 2018;Irastorza et al 2016;Kristman et al 2016;Marshall et al 1997). Branch is also an important contextual factor constituting economic conditions and future prospects influencing wages, job opportunities and job security (Irastorza et al 2016;Kristman et al 2016;Marshall et al 1997;Virtanen et al 2010). Branch may also be a relevant indicator of the gendered labour market, where a gender minority position may be protected as long as one is adhering to traditional gender norms, i.e.…”
Section: Occupational Working Conditions and The Contextual Factor Ofmentioning
confidence: 99%